Use of controlled nail dynamization technique for femoral shaft hypertrophic nonunion - Wu, Qian; Wang, Qi; Sun, XueCheng; Liu, Jun; Zhao, Gang; Yu, Ping (Frontiers in Surgery, 2025)
BackgroundFemoral nonunion after intramedullary nailing (IMN) of a diaphyseal long bone fracture is a severe complication that requires effective management. The IMN dynamization has been used to treat hypertrophic nonunions previously. However, routine nail dynamization has only a low success rate and the risk of limb shortening.MethodsTwo patients with femoral shaft fracture hypertrophic nonunion at 4 or 5 months after intramedullary nailing were treated with the therapeutic paradigm named “controlled nail dynamization”. In this paradigm, the interlocking nails are removed but the dynamic hole nails are retained. At the same time, four Poller screws were used to limit the movement of the intramedullary nail in the coronal and sagittal planes. The intramedullary nail can only generate compressive stress along the axial direction of the femoral shaft, thereby promoting fracture healing. So this technique was named “controlled nail dynamization”.ResultsHere, we describe two cases of delayed healing of the femoral diaphysis, which were successfully treated through controlled nail dynamization. Followed up for more than 12 months. Bone union was achieved in both patients, and there were no complications such as nonunion and internal fixation failure.ConclusionThe controlled nail dynamization is feasible for safe and effective treatment for femoral shaft hypertrophic nonunion.